"Smart vending machine" / Natasah Sudin, Ain Nadiah Ahmad and Hazirah Azami - Sudin, Natasah; Ahmad, Ain Nadiah; Azami, Hazirah (2018)
The product to be developing is Smart Vending Machine. The smart vending machine it can do incorporate function vending machine and oven. The product concept is fastening the process to get food. The product can deliver the item by frozen and cooked. It took 3 minutes to cook.